Optimizing MSMEs Digital Management and Marketing Through the KKU Service Program at O.N. Catering, Sidowayah Village Kabupaten Rembang - Syafi’i, Sherly Nanda; Werdhiana, Soraya Triska; Pratama, Elky Arkadia; Lukiarti, Ming Ming (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2025)
The Kuliah Kerja Usaha (KKU) program conducted by Universitas YPPI Rembang represents a practical implementation of the university's Tri Dharma through community service, focusing on empowering local micro, small, and medium enterprises (MSMEs). This particular project was carried out with O.N. Catering, a culinary MSME located in Rembang Regency. The program aimed to enhance the professionalism and competitiveness of the business by applying strategic digitalization and management practices. The methods employed included SWOT analysis, system design and development (rancang bangun), training, and mentoring. The implemented work programs consisted of the development of an administrative record book, a professional price list, promotional banners, online order forms via Google Forms, and business registration on Google Maps. These initiatives resulted in significant improvements in the MSME’s business structure, marketing reach, and digital visibility. The program demonstrated a sustainable impact by equipping the MSME with tools and strategies to adapt to modern business challenges.